Rimando identidades: raça, classe e periferia no rap maranhense. - RIBEIRO, Antônio Ailton Penha (2014)
This present work seeks to analyze the lyrics of Rap group ClãNordestino and Gíria Vermelha and the rapper PRC focusing on the categories of race, class and the periphery. The lyrics were treated as intellectual production of Mc’s, which enabled us to insert our analysis from the perspective of history of ideas espoused by Quentin Skinner. Our work has as its starting point the year of 2003, where it was released the first CD in the history of musical style in Maranhão with the group ClãNordestino and marc end the year 2008 with the release of the CD "A hora do Revide", the group Gíria Vermelha. The analysis of the lyrics of rappers points to a rhetorical attribute, but, above all, a practice that sees the radical transformation of society with a socialist revolution. Understanding the lyrics of the groups reviewed here contributes to the understanding of the ideas defended by the Hip Hop organized in the State of Maranhão.